Chick 'n' Pug - Sattler, Jennifer Gordon (New York : Scholastic, 2010)
Chick leaves the boring coop in order to find his hero, Wonder Pug, and a little bit of excitement.
H
b
M
Keywords: Roosters -- Fiction; Adventure and adventurers -- Fiction; Pug -- Fiction; Dogs -- Fiction